Development of localised electrochemical deposition control system for fabricating micro EDM electrode - Habib, Mohammad Ahsan; Saleh, Tanveer; Rahman, Mustafizur (Inderscience Enterprises Ltd, 2017)
Micro-EDM has become one of the most accepted advanced manufacturing technologies in micro-level fabrication. One of the main challenges in micro-EDM is to fabricate non-circular electrode. In order to overcome this challenge, this study presents a simple and inexpensive process to fabricate non-circular electrode by using localised electrochemical deposition (LECD). In this process, electrode was fabricated with the help of a non-conductive mask, which was placed between the anode and the cathode where the cathode was placed above the anode, and mask and the system was immersed in a plating solution of acidified copper sulphate. The micro-EDM was carried out by the deposited electrode without changing or removing its orientation. In order to fabricate high aspect ratio deposited electrode both open loop and close loop feedback system has applied. For comparing the two-control system, both the process was monitored during the time of deposition by measuring current density. It is found that, by using proper operating conditions and close loop control system high aspect ratio microstructure can be fabricated.